Thematic Learning Models with the Role-Playing Method in the Merdeka Curriculum in Inclusive Schools - Tarjiah, Indina; Wicaksono, Dirgantara; Aryani, Rita; Purnamawati, Siti Nuraini; Kurniawan, Erfan (Jurnal Pendidikan Indonesia, 2023)
The use of teaching strategies that interesting for all students by teachers is still lacking, especially for students who have indicators of slow learning.This study aims to develop a thematic learning model using role-playing techniques in inclusive schools. The Hannafin & Peck development model is adopted in this study along with the research and development methodology. The development phases are carried out starting with the needs analysis, design, development, and implementation stages. Processes for review and revision will be used in these three levels. Material and design experts have given developing thematic learning models utilizing the role-playing approach in the Merdeka curriculum in inclusive schools excellent marks for viability. Average material expert scores result in a score of 97.36%, whereas average design expert scores result in a score of 92.10%. The efficacy test results were then collected from 14 students, with an average score of 74.90% on the pretest. The posttest results, in comparison, had an average value of 85.14%. The development that has been done can be used by teachers at the inclusive schools to carry out teaching activities to students regarding thematic learning using the role-playing method in the Merdeka curriculum. This will ensure that the effectiveness test that was carried out was successful by getting an excellent. In order to realize government programs that provide inclusive education services that are friendly to all students.